Beyond western-oriented communication theories - Ayish, Muhammad I. (Javnost (Ljubljana), 2003)
For many decades, communication as a theoretical field of study has been dominated by Western-oriented perspectives that arose in the context of media perceptions in Western Europe and North America. Western communication theories have been promoted around the world as possessing a strong element of universalism. In recent years, this approach has been challenged on the basis of obfuscating the cultural peculiarities of non-Western societies as significant components of communication theorization. In this article, the author presents a normative Arab-Islamic perspective as a basis for future communication theory building in the Arab-Islamic context. Drawing on the notion of "Worldview," the Arab-Islamic perspective identifies four antithetical conceptual constructs that bear on the nature of communication: individualism-conformity, transcendentalism-existentialism, intuitive-rationalprocesses, and egalitarianism-hierarchy. The author concludes that Arab-Islamic communication patterns are formalistic, indirect, hyperbolic, asymmetrical, metaphysical and orally biased.
Keywords: arabske države; islam; komuniciranje; communication; sociologija komunikacij; komunikologija; communication sciences; komunikacijska teorija